Laparoscopic Transversus Abdominis Release, a Novel Minimally Invasive Approach to Complex Abdominal Wall Reconstruction. (April 2016) - Belyansky, Igor; Zahiri, H. Reza; Park, Adrian
Background . Open abdominal wall reconstruction is used to repair complex abdominal wall hernias with contour abnormalities. We present a novel minimally invasive approach to address these types of defects, completed entirely laparoscopically. Methods . Three patients underwent laparoscopic abdominal wall reconstruction for complex hernias in August and September of 2015. Operative approach consisted of laparoscopic transversus abdominis components separation, defect closure, and wide mesh implantation in the retromuscular space. Results . Two males and one female with mean age and body mass index of 70 and 30.1, respectively, underwent a mean operation room time of 329 minutes. Estimated blood loss and length of stay were 91.7 cc and 4.7 days, respectively. No subcutaneous flaps were raised avoiding the need for subcutaneous drains. There were no perioperative complications. All of the subfascial drains were removed prior to patient discharge. On initial follow-up visit at 3 weeks, there was no evidence of wound complications, bulging, or hernia recurrences. Conclusion . Laparoscopic abdominal wall reconstruction with transversus abdominis release is a unique and feasible approach to complex abdominal wall defects with the potential to reduce pain, facilitate recovery, and decrease length of hospital stay for patients.